My friend Rabbit - Rohmann, Eric. (New Milford, Conn. : Roaring Brook Press, 2002)
Something always seems to go wrong when Rabbit is around, but Mouse lets him play with his toy plane anyway because he is his good friend.
Wilson's Children, October 2010.
Notable/Best Books (A.L.A.), January 2003.
School Library Journal, May 2002.
Publisher's Weekly, April 2002.
Booklist, May 2002.
New York Times, May 2003.
Keywords: Friendship -- Fiction; Rabbits -- Fiction; Mice -- Fiction; Friendship -- Fiction; Rabbits -- Fiction; Mice -- Fiction; Friendship -- Fiction; Rabbits -- Fiction; Mice -- Fiction; Animals -- Fiction